Evaluation of the college-based HIV/AIDS education policy in Beijing, China: a mixed method approach - Yunting Zheng; Xin Zhang; Xinying Sun; Yuhui Shi; Chun Chang (Komiyama Printing Co. Ltd, 2020)
Abstract Background From 2010 to 2015, there was a twofold growth of new HIV/AIDS infection in Beijing among young students aged 15-24. HIV/AIDS education was found effective in promoting positive behavior change related to HIV/AIDS prevention. However, little evidence was found on the evaluation of HIV/AIDS education policy. This study aimed to evaluate the college-based HIV/AIDS education policy in Beijing. Methods By using a mixed method approach, the current study reviewed college-based HIV/AIDS education policy at national level and in Beijing from 1985 to 2016 and conducted policy content analysis to evaluate the policy ability to structure implementation. Cross-sectional surveys in 2006 and 2016 were used to evaluate college's implementation of relevant policies. T test, χ 2 test, and logistic regression were used to analyze college students' perception of HIV/AIDS education provided in their colleges and their knowledge of HIV/AIDS and their risk factors. Results Fourteen pieces of national policy and four pieces of Beijing's policy were identified. Policy's ability to structure implementation was at moderate level. The percentage of students in Beijing who ever perceived HIV/ADIS education at colleges decreased from 71.14 to 39.80%, and the percentage of students with comprehensive knowledge of HIV/AIDS dropped from 50.00% in 2006 to 40.42% in 2016. Conclusions HIV/AIDS education in college had drawn considerable attentions from the Chinese government, while the policy implementation needs further strengthening.